2017
DOI: 10.1515/odps-2017-0015
|View full text |Cite
|
Sign up to set email alerts
|

Large Scale Liquid Crystal Device with Graphene-based Electrodes

Abstract: Abstract:The new generation Liquid-Crystal Displays (LCDs) will play a key role in modern display industry thus the requirements concerning the response time, power consumption, viewing angles, contrast ratio and easy production stay beyond challenging. In this paper we demonstrate fabrication of large scale liquid crystal device with graphene-based electrodes using a photo-alignment technique. The quality of graphene layer, grown by low pressure CVD method and transferred on the glass substrates was character… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Within these technologies, graphene has been used as an ITO replacement in standard [230,231] and flexible [232][233][234] OLED displays. Graphene has also been used in flexible alternating-current electroluminescent displays [235][236][237], as well as in LCDs [238][239][240]. Other applications of graphene in display technologies include increasing standard ITO OLED performance [241] and using as electrodes for GaN micro-LEDs [242].…”
Section: Applicationsmentioning
confidence: 99%
“…Within these technologies, graphene has been used as an ITO replacement in standard [230,231] and flexible [232][233][234] OLED displays. Graphene has also been used in flexible alternating-current electroluminescent displays [235][236][237], as well as in LCDs [238][239][240]. Other applications of graphene in display technologies include increasing standard ITO OLED performance [241] and using as electrodes for GaN micro-LEDs [242].…”
Section: Applicationsmentioning
confidence: 99%
“…One particular application of graphene is its use as a transparent conducting electrode (TCE) in devices such as solar cells, displays or wearable electronics, by leveraging its high optical transparency, electrical conductivity, chemical stability and mechanical strength [14]. Absorbing only 2.3% of the impinging lightwave in the visible (VIS) and near-infrared (NIR) spectrum, single-layer graphene has been demonstrated, for instance, as a viable and lower-cost substitute to indiumtin-oxide (ITO) in VIS/NIR liquid-crystal (LC) modulators [15][16][17]. More importantly, graphene can provide TCE solutions in lower-frequency parts of the electromagnetic spectrum where ITO is opaque, such as in the emerging field of terahertz (THz) technology.…”
Section: Introductionmentioning
confidence: 99%
“…Such LC cells have two major components: the indium tin oxide (ITO) electrodes and the polyimide (PI) alignment layers. Since MGP has a few advantages over ITO electrodes, such as better mechanical strength, higher chemical resistance, and higher mechanical flexibility, several reports in the literature have shown that MGP can serve as an ITO replacement in an LC device [11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%